DINAMIKA KEWIRAUSAHAAN DAN PENDIDIKAN DIPONDOK PESANTREN SUNAN DRAJAT LAMONGAN - Salsabilla, Aliffia Rahma Putri (Program Studi Sejarah Peradaban Islam Fakultas Ushuluddin Adab dan Dakwah IAIN Manado, 2024)
This article was created to reveal the education system and tips carried out by Sunan Drajat Islamic boarding school in empowering the entrepreneurial spirit of students. This Islamic boarding school located in Lamongan Regency, East Java was established in 1977. Although it has not yet formulated a century, this pesantren already has several thousand alumni. The students at Sunan Drajat Islamic boarding school are not only equipped with education, but also equipped with entrepreneurial knowledge. Through a deep understanding of the educational environment of Islamic boarding schools, student perceptions, and entrepreneurial characteristics, new research results can be produced related to the development of effective strategies to foster entrepreneurial spirit among Sunan Drajat Islamic boarding school students. In compiling the results of the study, researchers obtained data through two sources, namely primary sources in the form of official websites belonging to pesantren and secondary sources in the form of theses, and assisted by several scientific journals. In the education system, Sunan Drajat Islamic Boarding School is divided into two, namely formal and non-formal. An interesting thing that was discussed was the efforts of the Islamic Boarding School in empowering the entrepreneurial spirit of the students. In its application, students are directly involved in entrepreneurial activities owned by pesantren. The entrepreneurial forms of Sunan Drajat Islamic boarding school include agriculture, beverages, biodiesel fuel, and many others. The purpose of the entrepreneurial provision is none other than to be a provision for students when leaving the pesantren.